2016
DOI: 10.1038/srep22170
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Cortical Brain-Machine Interface for Whole-Body Navigation in Primates

Abstract: Several groups have developed brain-machine-interfaces (BMIs) that allow primates to use cortical activity to control artificial limbs. Yet, it remains unknown whether cortical ensembles could represent the kinematics of whole-body navigation and be used to operate a BMI that moves a wheelchair continuously in space. Here we show that rhesus monkeys can learn to navigate a robotic wheelchair, using their cortical activity as the main control signal. Two monkeys were chronically implanted with multichannel micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 51 publications
0
55
0
2
Order By: Relevance
“…These have been developed to bypass motor lesions (assistive BMIs) (Wolpaw and McFarland, 1994; Kennedy and Bakay, 1998; Leuthardt et al, 2004; Moritz et al, 2008; Ethier et al, 2012; Collinger et al, 2013; Memberg et al, 2014; Jarosiewicz et al, 2015; Bouton et al, 2016; Capogrosso et al, 2016; Hotson et al, 2016; Rajangam et al, 2016; Vansteensel et al, 2016; reviewed in Lobel and Lee, 2014) and, more recently, to facilitate neural plasticity and motor learning to enhance recovery after injury (rehabilitative BMIs) (Carhart et al, 2004; Buch et al, 2008; van den Brand et al, 2012; Ang et al, 2013; Ramos-Murguialday et al, 2013; Wahl et al, 2014; Gharabaghi et al, 2014a,b,c; Gerasimenko et al, 2015b; Donati et al, 2016; reviewed in Ethier et al, 2015; Jackson and Zimmermann, 2012). …”
Section: The Neurophysiology Underlying Brain-machine and Neural Intementioning
confidence: 99%
See 2 more Smart Citations
“…These have been developed to bypass motor lesions (assistive BMIs) (Wolpaw and McFarland, 1994; Kennedy and Bakay, 1998; Leuthardt et al, 2004; Moritz et al, 2008; Ethier et al, 2012; Collinger et al, 2013; Memberg et al, 2014; Jarosiewicz et al, 2015; Bouton et al, 2016; Capogrosso et al, 2016; Hotson et al, 2016; Rajangam et al, 2016; Vansteensel et al, 2016; reviewed in Lobel and Lee, 2014) and, more recently, to facilitate neural plasticity and motor learning to enhance recovery after injury (rehabilitative BMIs) (Carhart et al, 2004; Buch et al, 2008; van den Brand et al, 2012; Ang et al, 2013; Ramos-Murguialday et al, 2013; Wahl et al, 2014; Gharabaghi et al, 2014a,b,c; Gerasimenko et al, 2015b; Donati et al, 2016; reviewed in Ethier et al, 2015; Jackson and Zimmermann, 2012). …”
Section: The Neurophysiology Underlying Brain-machine and Neural Intementioning
confidence: 99%
“…Means of extracting nervous system signals range from invasive [intracortical microelectrodes (APs, or spikes) and larger scale sub- or epidural electrodes (electrocorticography, ECoG)] to non-invasive [electroencephalography (EEG) or electromyography (EMG)]. Targeted outputs have included cursors on a screen (Wolpaw and McFarland, 1994; Kennedy and Bakay, 1998; Leuthardt et al, 2004; McFarland et al, 2010), virtual typing (Jarosiewicz et al, 2015), robotic or prosthetic arms (Collinger et al, 2013; Hotson et al, 2016), wheelchairs (Rajangam et al, 2016), exoskeletons (Donati et al, 2016), the spinal cord (Zimmermann and Jackson, 2014; Capogrosso et al, 2016), and a patient's own extremities (Ethier et al, 2012; Memberg et al, 2014; King et al, 2015; Bouton et al, 2016; Vidaurre et al, 2016). …”
Section: The Neurophysiology Underlying Brain-machine and Neural Intementioning
confidence: 99%
See 1 more Smart Citation
“…Those studies focused on locomotion (Capogrosso et al, 2016;Foster et al, 2014;Yin et al, 2014), vocalization (Hage & Jurgens, 2006;Roy & Wang, 2012), or showed proof-of-concept data of sleep (Yin et al, 2014) or basic uninstructed behavior (Fernandez-Leon et al, 2015;Gilja et al, 2010;Schwarz et al, 2014). One study used a wireless brain-machine-interface to let monkeys control a robotic wheelchair in which they sat (Rajangam et al, 2016). Other studies used tethered recordings to investigate primates freely exploring the environment while being attached to a pole (Sun et al, 2006), to a cable assembly (Ludvig et al, 2004) or seated in a chair they could move (Rolls, Robertson, & Georges-François, 1997).…”
Section: Neural Recordings In Unrestrained Non-human Primatesmentioning
confidence: 99%
“…2) 7 . Using their neural activity as a control signal, the monkeys learned to drive the chairs and navigate towards fruit rewards.…”
Section: Translation To Human Patientsmentioning
confidence: 99%